Gamle ordbøker og digitale utgaver - Ore, Christian-Emil Smith (Nordiske Studier i Leksikografi, 2018)
Today it is relatively easy to re-publish old dictionaries on the web based on retro digitized text. To create trustworthy editions which can serve as the fundament for reliable Linked Data, this has to be done with care and it is necessary to follow the basic principles of digital scholarly text edi-tions. A digital edition of the Norwegian Dictionary written by the Nor-wegian linguist Ivar Aasen published in 1873 is used as example.